Perceived Risk Reduction Strategies for Organic Food Customers. Issue 5 (12th June 2020) - Pandey, Shivendra Kumar; Gupta, Ashish Kumar; Sharma, Dheeraj P.
ABSTRACT: The present study attempts to compare and contrast the organic food choice-making process among high and low-income customers based on food quality, service quality and price fairness. Data were collected through structured questionnaires and analyzed using structural equation modeling. The results indicate apparent differences in decision-making strategies of high and low-income customers. Price fairness played an essential role in reducing risk and enhancing trust among low-income customers. Therefore, perceived risk reduction strategies are more suited for low-income consumers. For high-income consumers, trust was crucial. Also, product and service quality was equally vital for both segments. Managers selling organic food to high-income customers should focus on the retailing mix elements to build trust in the retailer. However, for low-income customers, managers should justify the price premium as fair. Also, managers may try to reduce financial risk by mechanisms such as money-back guarantees or liberal return policies for low-income customers.